Aplicación del juego simbólico en la convivencia escolar en los niños de cuatro años de la Institución Educativa Inicial N°705 Punchana 2024 - Peña Ismiño, Heyla Pierina (2025)
The purpose of this study was to determine the relationship of the application of symbolic play in school coexistence in four-year-old children of the Initial Educational Institution N°705, Punchana 2024. In order to achieve the objective of this research, has adopted by applying a quantitative research approach to address the topic at hand; The type of research selected for this study is relational; Likewise, in this study, a non-experimental, correlational and cross-sectional research design has been adopted to address the proposed research topic. The population under study was made up of 83 four year-old children from the Initial Educational Institution N°705, Punchana 2024, as instruments for data collection, observation techniques were used, supported by an observation guide, and the instruments obtained were validated through the evaluation of three experts. The results indicate a Spearman's Rho test correlation coefficient of 0.732 and a p value of 0.05. This finding suggests that symbolic play has an important relationship in improving school coexistence. Therefore, it is concluded that there is a significant positive relationship between the application of symbolic play and school coexistence in four-year-old children.